DEVELOPMENT OF LEARNING KIT 'KOMPUTER KAMI' AND THE USAGE IMPACT WITHIN CHILDREN WITH SPECIAL NEEDS (Proceedings of International Conference on Special Education, 2017)
“Komputer Kami Learning Kit” are a combination of teaching aids using the mobile application in android environment, a workbook by level of cognitive and Tarsia puzzle game. Applications' “Komputer Kami” developed using Adobe Flash for the topic "Know Your Computer Parts" on the syllabus of Multimedia in Special Education Curriculum for Learning Disabilities . The selection of technology can help reduce constraints, limitations and difficulties faced by special education teachers to integrate elements of entertainment and education to be more fun and interesting for them to learn. In addition, environmental factors that influence the students' use of applications using tablet computers in the learning process also noteworthy because these factors greatly influence the effectiveness of the use of tablet computers among students with Special Needs (SEN) towards 21st Century Education. Pre and post test data was analyzed using SPSS version 18 for the mean value of the marks obtained by the students. The findings showed that student achievement increased by 25.48% ( Pre Test mean = 55.08%, Post Test Mean = 80.56%). While the T test showed no significant difference between the two mean scores on the significance level of 0.05. The conclusions of this study, has been able to improve the students‟s skills master the learning objectives. This approach has the potential to be further extended